2006
DOI: 10.1210/me.2005-0479
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Activation of the Sterol Regulatory Element-Binding Protein Pathway: Current Insights

Abstract: The cellular effects of androgens are mediated by a cognate receptor, the androgen receptor. Typically, the androgen receptor is viewed to exert its activity by binding to androgen response elements located in or near the promoter region of target genes, thereby directly affecting the expression of these genes. However, increasing evidence indicates that androgens may also indirectly influence the expression of genes that do not contain androgen response elements by modulating the activity of secondary transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 93 publications
5
104
0
Order By: Relevance
“…In response to the ␤2M-mediated cell signaling, SREBP-1 regulated AR expression by altering AR gene transcription. Conversely, androgens and AR were also found to mediate SREBP-1 expression reciprocally in androgen-responsive prostate cancer cells (40,41). These data, taken together with previous reports from our laboratory and others that documented the regulatory role of ␤2M on AR expression (10) and also androgens and AR regulation of ␤2M expression (8), support the triad relationship among ␤2M, SREBP-1, and AR.…”
Section: Discussionsupporting
confidence: 83%
“…In response to the ␤2M-mediated cell signaling, SREBP-1 regulated AR expression by altering AR gene transcription. Conversely, androgens and AR were also found to mediate SREBP-1 expression reciprocally in androgen-responsive prostate cancer cells (40,41). These data, taken together with previous reports from our laboratory and others that documented the regulatory role of ␤2M on AR expression (10) and also androgens and AR regulation of ␤2M expression (8), support the triad relationship among ␤2M, SREBP-1, and AR.…”
Section: Discussionsupporting
confidence: 83%
“…All SREBP isoforms are activated when an escort protein, SCAP, facilitates migration to the Golgi apparatus (34). It is known that androgens up-regulate SCAP mRNA expression, thus promoting SREBP activation (35). This is confirmed in Fig.…”
Section: The Ar Does Not Influence Lxr Expression or Lxr-dnasupporting
confidence: 59%
“…LXR differentially influences cholesterol and fatty acid homeostasis; while LXR promotes cholesterol depletion, it promotes fatty acid synthesis by directly up-regulating FASN and SREBP-1c expression. Thus, the AR-LXR antagonism should negatively influence SREBP-1c activity, but the AR also promotes SREBP-1c activation by increasing SCAP mRNA levels (35). We found that androgen treatment increased FASN expression and had little influence on SREBP-1c expression (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Androgen regulation of steroid-biosynthesis genes is mediated through an indirect mechanism involving the activation of sterol regulatory-element binding proteins SREBP-1 and SREBP-2 (Heemers et al, 2006). Further, kruppel-like factor 5 (KLF5) has recently been identified as an androgen-regulated gene that acts as a positive regulator of SREBP-1 function (Lee et al, 2009).…”
Section: Resultsmentioning
confidence: 99%